2008
DOI: 10.1007/s00392-008-0664-7
|View full text |Cite
|
Sign up to set email alerts
|

Hotline update of clinical trials and registries presented at the German Cardiac Society meeting 2008

Abstract: This review article summarizes results of a number of new clinical trials and registries in the field of cardiovascular medicine. Key presentations made at the 74th annual meeting of the German Cardiac Society, held in Mannheim, Germany, in March 2008 are reported. The data were presented by leading experts in the field with relevant positions in the trials and registries. These comprehensive summaries should provide the readers with the most recent data on diagnostic and therapeutic developments in cardiovasc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…The data were presented by leading experts in the field with relevant positions in the trials and registries. These comprehensive summaries should provide the readers with the most recent data on diagnostic and therapeutic developments in cardiovascular medicine similar as previously reported (Rosenkranz et al in Clin Res Cardiol 96:457–468, 9; Maier et al in Clin Res Cardiol 97:356–363, 3). …”
supporting
confidence: 57%
See 2 more Smart Citations
“…The data were presented by leading experts in the field with relevant positions in the trials and registries. These comprehensive summaries should provide the readers with the most recent data on diagnostic and therapeutic developments in cardiovascular medicine similar as previously reported (Rosenkranz et al in Clin Res Cardiol 96:457–468, 9; Maier et al in Clin Res Cardiol 97:356–363, 3). …”
supporting
confidence: 57%
“…The objective of the GERSHWIN (German stent health outcome and economics within normal practice) study was to study clinical benefit (MACE: death, myocardial infarction, bypass therapy, re-PCI in the target vessel), costs, and quality of life using SES or BMS [3]. Patients were allocated in a 2:1 fashion to SES or BMS from 2003 to 2005 in 35 centers across Germany.…”
Section: Gershwinmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were presented by leading experts in the field with relevant positions in the trials and registries. These comprehensive summaries should provide the readers with the most recent data on diagnostic and therapeutic developments in cardiovascular medicine similar as previously reported 9;3).…”
mentioning
confidence: 53%
“…Most of the scientific evidence regarding DEB efficacy is actually concentrated in the treatment of patients with in-stent restenosis; there are some data about use of DEBs for de novo lesions and for bifurcation lesions [9]. For de novo lesions the only registry available is the Paclitaxel-Eluting PTCA-Balloon Catheter to Treat Small Vessel Coronary Artery Disease (PEPCAD I), which concluded that DEBs are associated with a high procedural success rate in small de novo lesions, while DEBs in conjunction with a bare-metal stent (BMS) remains a concern because of high restenosis rate [10]. Until now, DEBs failed to show equivalence to DES regarding angiographic endpoints during PCI of small coronary arteries [11].…”
Section: Introductionmentioning
confidence: 99%